Historical Analysis and Conflicting Perspectives: Contextualising HCI - Bødker, Susanne (DAIMI Report Series, 1993)
This paper develops two ways of analyzing the human-computer interaction of a computer application in use in an organization. The techniques, historical analyses and conflicting perspectives analysis, and the interplay between them, are used in providing the basis for a more detailed analysis. Historical analyses focus on the historical development of artifacts and their use. Conflicting perspectives analysis reflects on the roles of the artifact in use, as system, tool, or medium. Combined, the two types of analysis allow for a focus in particular on conflicts between the roles of a specific artifact in use. The techniques are based on human activity theory. They are illustrated by means of a case study of a computer application from a project with the Danish National Labour Inspection Service.